Use of DNA barcode in the identification of catfishes (Siluriformes: Ariidae) from Malaysia - MOHD LUTFI ABDULLAH; SITI AZIZAH MOHD NOR; DARLINA MD. NAIM (Biodiversitas Journal of Biological Diversity, 2017)
Abdullah ML, Nor SAM, Naim DMd. 2017. Use of DNA barcode in the identification of catfishes (Siluriformes: Ariidae) from Malaysia. Biodiversitas 18: 1358-1366. The genus Ariidae contains many valuable fish species threatened by overfishing, but knowledge on distribution and threats is still limited due to taxonomic ambiguities. The aim of this study was to apply DNA barcoding techniques to establish a resource of DNA for identification of Ariidae species in Malaysia. A 621 bp of mitochondrial cytochrome oxidase subunit I (COI) gene was utilized to resolve phylogenetic relationships and molecular taxonomy of eight presumed Malaysian Ariid species. We found the monophyly of most species was well established with a mean Kimura-2 parameter (K2P) interspecies distance of 9.6% except for two species, Arius venosus, and Nemapteryx caelata that have very low interspecies genetic distance. The BLAST result shows only two species matched the presumably eight identified fish species. Such discrepancies could arise as a result of misidentifications or errors in GenBank database input, hybridization or incomplete lineage sorting. We suggest the use of DNA barcoding is integrated into the workflow during taxonomic studies as it could significantly increase knowledge about species distributions.